Activity of trypsin inhibitors in common bean seeds (Phaseolus vulgaris L.) from the VIR collection: variability and source material for breeding - T. V. Buravtseva; G. P. Egorova; M. O. Burlyaeva; M. A. Nikishkina (Труды по прикладной ботанике, генетике и селекции)
Background. An important trend in modern common bean breeding is the improvement of grain quality, including by reducing the content of anti-nutrients, so it is important to identify accessions that are free of inhibitors or contain minimal amounts of them. The search for samples with high content of inhibitors is also relevant, since inhibitors play a crucial role in the functioning of the basic biochemical mechanisms that determine and regulate the physiological state of the cell.Materials and methods. Presented here are the results of biochemical and field screening of 141 common bean accessions (Phaseolus vulgaris L.) of different ecogeographic origin from the collection of VIR. Various sets of accessions were grown at VIR's experimental stations - Krymsk Experiment Breeding Station, branch of VIR (Town of Krymsk); Pushkin and Pavlovsk Laboratories of VIR (City of St. Petersburg) - in 2000-2003. Field study of economically valuable traits was carried out according to VIR's methods. Trypsin inhibitor activity (TIA) was calculated at the biochemical laboratory of VIR by spectrophotometry. The program Statistica 7.0. (StatSoft, Inc., USA) was used for statistical analysis.Results. TIA assessment in the seeds of common bean accessions showed that the mean value of the trait varied depending on the country of origin and the year of study. The results of the correlation analysis showed that the values of correlation coefficients were unstable over the years of study, and did not allow us to reveal stable relationships between TIA in bean seeds and meteorological conditions (-0.39 ≤ r ≤ 0.41), morphological (0.03 ≤ r ≤ 0.23) and economically valuable (-0.05 ≤ r ≤ 0.21) traits. The analysis of variance showed that the content of trypsin inhibitors in seeds depends more on the genetic properties of plants (effect-size percentage is 88.6%), less on weather conditions (12.24-20.16%), the year of reproduction (20.16%) or origin (18.87%), and only to a small extent on the place of reproduction (10.76%).Conclusions. The study helped to find 8 sources of low TIA (< 7 mg/g), and 25 ones with high TIA (> 13 mg/g). Accessions combining high seed protein content (> 30%) with low (< 7 mg/g) or medium (7-9 mg/g) TIA levels were also identified. Those accessions can be included in future breeding programs. The lowest mean TIA values were observed in the accessions from Azerbaijan (7.55), Madagascar (8), Costa Rica (8.05), and Denmark (8.98), while high mean TIA was manifested by the accessions from Bhutan (17.8), Russia (13.4), Kenya (13.2), and Sweden (12, 97). The correlation analysis failed to reveal stable interrelations between TIA and meteorological conditions or morphological and economically valuable traits. The TIA level basically depends on the genetic properties of plants.